A people's history of the United States - Zinn, Howard, 1922-2010 (Harper Perennial modern classics., 2015)
"With a new introduction by Anthony Arnove, this edition of the classic national bestseller chronicles American history from the bottom up, throwing out the official narrative taught in schools--with its emphasis on great men in high places-- to focus on the street, the home, and the workplace. Known for its lively, clear prose as well as its scholarly research, A People's History of the United States is the only volume to tell America's story from the point of view of--and in the words of--America's women, factory workers, African-Americans, Native Americans, the working poor, and immigrant laborers. As historian Howard Zinn shows, many of our country's greatest battles--the fights for a fair wage, an eight-hour workday, child-labor laws, health and safety standards, universal suffrage, women's rights, racial equality--were carried out at the grassroots level, against bloody resistance. Covering Christopher Columbus's arrival through President Clinton's first term, A People's History of the United States, which was nominated for the American Book Award in 1981, features insightful analysis of the most important events in our history" --